2010 Third IEEE International Conference on Digital Game and Intelligent Toy Enhanced Learning 2010
DOI: 10.1109/digitel.2010.40
|View full text |Cite
|
Sign up to set email alerts
|

TeMPS: A Conceptual Framework for Pervasive and Social Games

Abstract: Abstract-Pervasive and social game is an emerging game genre which brings more physical movement and social interactions into game. This article proposes the conceptual framework TeMPS that systematically characterize the important aspects of pervasive and social games. Further, around thirty games in different sub-genres are reviewed by analyzing and fitting them into the framework. The framework is helpful for game designers to understand and communicate about such games. Further, it contributes to conceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…• Interactive experiences (Benford & Giannachi, 2008;Mitchell & Olsson, 2018;Wouters et al, 2016) • Playful experiences (Arrasvuori et al, 2011;Lucero & Arrasvuori, 2013 • Mixed reality experiences and games (Hinske et al, 2007;Wetzel et al, 2017) • Pervasive games and experiences (Arango-López et al, 2019Benford et al, 2005;Guo et al, 2010;Hinske et al, 2007;Jegers, 2007Jegers, , 2009Magerkurth et al, 2005;Montola, 2005;Nieuwdorp, 2007;Walther, 2005Walther, , 2011Walz & Ballagas, 2007) • Urban games and experiences (Mitchell & Olsson, 2018;Wouters et al, 2016) • Location-based/location-aware games and experiences (Broll & Benford, 2005;Maia et al, 2017;Neustaedter et al, 2013;Walz & Ballagas, 2007) • Ubiquitous games (Chalmers et al, 2005;McGonigal, 2006) • Alternate Reality Experiences (Gutierrez et al, 2011;Hansen et al, 2013;Kourouthanassis et al, 2015) • Shared interactive narratives (Benford & Giannachi, 2008) • Augmented reality experiences (Gutierrez et al, 2011;Kourouthanassis et al, 2015) Walther collects a number of these under the broader genre of pervasive games: incorporating mobile games, location-based games, ubiquitous games, virtual reality games & augmented reality games where each shares the key characteristics of "(1) the explicitness of computational tasks; and (2) the overall importance of physical space" (2005, p. 4). On the other hand, others bring pervasive games and experiences under the umbrella of mixed reality experiences (Hinske et al, 2007;…”
Section: Challengesmentioning
confidence: 99%
“…• Interactive experiences (Benford & Giannachi, 2008;Mitchell & Olsson, 2018;Wouters et al, 2016) • Playful experiences (Arrasvuori et al, 2011;Lucero & Arrasvuori, 2013 • Mixed reality experiences and games (Hinske et al, 2007;Wetzel et al, 2017) • Pervasive games and experiences (Arango-López et al, 2019Benford et al, 2005;Guo et al, 2010;Hinske et al, 2007;Jegers, 2007Jegers, , 2009Magerkurth et al, 2005;Montola, 2005;Nieuwdorp, 2007;Walther, 2005Walther, , 2011Walz & Ballagas, 2007) • Urban games and experiences (Mitchell & Olsson, 2018;Wouters et al, 2016) • Location-based/location-aware games and experiences (Broll & Benford, 2005;Maia et al, 2017;Neustaedter et al, 2013;Walz & Ballagas, 2007) • Ubiquitous games (Chalmers et al, 2005;McGonigal, 2006) • Alternate Reality Experiences (Gutierrez et al, 2011;Hansen et al, 2013;Kourouthanassis et al, 2015) • Shared interactive narratives (Benford & Giannachi, 2008) • Augmented reality experiences (Gutierrez et al, 2011;Kourouthanassis et al, 2015) Walther collects a number of these under the broader genre of pervasive games: incorporating mobile games, location-based games, ubiquitous games, virtual reality games & augmented reality games where each shares the key characteristics of "(1) the explicitness of computational tasks; and (2) the overall importance of physical space" (2005, p. 4). On the other hand, others bring pervasive games and experiences under the umbrella of mixed reality experiences (Hinske et al, 2007;…”
Section: Challengesmentioning
confidence: 99%
“…Typical pervasive games have features such as location awareness, using physical user interfaces, mobility and long lasting. In our previous research, more characteristics were summarized [21]. In Reference [22], the authors indicated that pervasive games aimed at combining the properties and advantages of three worlds: the physical worlds, social worlds, and virtual worlds.…”
Section: Pervasive Gamementioning
confidence: 99%
“…In addition to general computer games, PerGO should also support special features of pervasive games. In one earlier research of ours, more than 30 pervasive games were reviewed and the main characteristics of pervasive games were summarized in one conceptual framework named TeMPS [21]. While TeMPS was designed to understand and analyze pervasive games, PerGO is designed to construct pervasive games.…”
Section: The Effectiveness Of Vocabularymentioning
confidence: 99%
“…Additionally, in [Guo et al 2010], there is a description of a framework, called "TeMPS", named for the four identified perspectives and that are also part of the pervasive game design: temporality, mobility, perceptibility and sociability. Finally, [Chatzigiannakis et al 2010] lists some factors that are required for the implementation of a pervasive game.…”
Section: Introductionmentioning
confidence: 99%